Evaluasi Layanan Difabel Tunanetra di Dinas Perpustakaan dan Kearsipan Kabupaten Sleman - Irzalina Rahmawati; Thoriq Tri Prabowo (Perpustakaan Nasional, 2019)
This study aims to study the evaluation of library services for persons with disabilities in the Sleman Regency Public Library. This research is a qualitative research. Data collection methods are observation, interview, and observation. The results of this study are; There are three standard service components issued by IFLA namely physical access, media format, services, and computers. Some Library Services already meet the standards, but there are some services that do not meet the standards. Sleman Regency Library needs to pay more attention to this matter. Based on these three components, the Sleman Regency Library and Archives Service has braille corner for users with visual impairments. However, it is better if braille in the library is not fully utilized by the user. So the library then needs to hold a socialization activity so that the braille angle can be utilized to its full potential in accordance with the information needs of the visually impaired community. The findings of this study are that the Sleman Regency Public Library has actually provided services for people with visual impairments, but this service has not been optimally managed. This study adds to the Library or Librarian to disseminate information to the public about braille corner services so that they can be utilized optimally.